2001
DOI: 10.1002/gps.424
|View full text |Cite
|
Sign up to set email alerts
|

Bupropion SR in the naturalistic treatment of elderly patients with major depression

Abstract: In this naturalistic 12-week study, geriatric MD patients with high and low medical comorbidity responded well to bupropion and bupropion SR. In elderly patients, four to eight week acute treatment periods may be insufficient. Our findings suggest that nearly 50% of elderly depressed subjects at a tertiary center may need combination therapy over the course of their illness. Controlled randomized studies to establish the long-term efficacy and optimal dose of the newer antidepressants in geriatric depression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…The statistics in Table 1 and Table 2 are derived on the basis of cumulative frequencies of any response (MADRS Ͻ16), of remission (MADRS Ͻ7), and relapse (MADRS Ͼ15) at fixed 3-month intervals up to 18 months. 24,25 We used Kaplan-Meier estimates to estimate the percentage of patients achieving remission. These definitions may differ from those suggested for use in controlled treatment trials.…”
Section: Discussionmentioning
confidence: 99%
“…The statistics in Table 1 and Table 2 are derived on the basis of cumulative frequencies of any response (MADRS Ͻ16), of remission (MADRS Ͻ7), and relapse (MADRS Ͼ15) at fixed 3-month intervals up to 18 months. 24,25 We used Kaplan-Meier estimates to estimate the percentage of patients achieving remission. These definitions may differ from those suggested for use in controlled treatment trials.…”
Section: Discussionmentioning
confidence: 99%
“…Covariates were included to examine their contribution to associations between year and dementia prevalence. After reviewing large population-based studies and systematic reviews of risk factors and risk models for dementia (6,(15)(16)(17)(18)(19)(20)(21), the following covariates were included in the models based on their associations with dementia in previous studies and based on the data available in the dataset: age, sex, location (state) and reported health conditions (cerebrovascular disease including stroke, diabetes, hypertension, ischaemic heart disease, high cholesterol, obesity, malnutrition, depression, alcohol abuse/dependence and head injury).…”
Section: Covariatesmentioning
confidence: 99%
“…These mean scores represent all person observations for a particular time period, i.e., a subject may contribute more than one MADRS during a given time period. Relevant scores reported for the MADRS include a score below 15 to define a response, and a score below 7 to define remission (Bosworth et al, 2002;Steffens et al, 2001b).…”
Section: The Sample: Characteristics and Follow-upmentioning
confidence: 99%